FOXD3-AS1 Knockdown Suppresses Hypoxia-Induced Cardiomyocyte Injury by Increasing Cell Survival and Inhibiting Apoptosis via Upregulating Cardioprotective Molecule miR-150-5p In Vitro - Zheng, Jiayong; Peng, Bangtian; Zhang, Yanwei; Ai, Feng; Hu, Xiaosong (Frontiers in Pharmacology, 2020)
Congenital heart disease (CHD) is the most common type of human innate malformation in fetuses. LncRNAs have been pointed to play critical regulatory roles in various types of cardiac development and diseases including CHD. Our study aimed to explore the effects of lncRNA forkhead box D3 antisense RNA 1 (FOXD3-AS1) on hypoxia-induced injury in AC16 cardiomyocytes and the related molecular mechanism. In vitro cell model of CHD was established by stimulating AC16 cells with hypoxia (1% O2). Expression of FOXD3-AS1 and miR-150-5p was detected by qRT-PCR. Hypoxia-induced injury was evaluated by detecting cell survival, lactate dehydrogenase (LDH) release, apoptosis, and caspase-3/7 activity using MTT, LDH assay, flow cytometry analysis, and caspase-3/7 activity assay, respectively. The regulatory relationship between FOXD3-AS1 and miR-150-5p was explored by luciferase reporter assay, RNA immunoprecipitation (RIP), and qRT-PCR. Results showed that hypoxia exposure caused an upregulation of FOXD3-AS1 and a downregulation of miR-150-5p in AC16 cells. Knockdown of FOXD3-AS1 attenuated reduction of cell survival and increase of LDH release, apoptosis, caspase-3/7 activity, and Bcl-2 associated X (Bax) expression induced by hypoxia in AC16 cells. Notably, we demonstrated that FOXD3-AS1 directly interacted with miR-150-5p to inhibit its expression. miR-150-5p knockdown reinforced the reduction of survival and induction of apoptosis by hypoxia and attenuated the effects of FOXD3-AS1 silencing on the same parameters in AC16 cells. In conclusion, FOXD3-AS1 knockdown protected AC16 cardiomyocytes from hypoxia-induced injury by increasing cell survival and inhibiting apoptosis through upregulating miR-150-5p.